Efektivitas Sleep Hygiene dan Terapi Guided Imagery terhadap Kecemasan dan Nyeri Pasien Kanker Payudara yang Menjalani Kemoterapi - Shabrina Isma Rasyida; Retno Setyawati; Suyanto, Suyanto (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Breast cancer is a type of cancer that is often experienced by women and is generally treated with chemotherapy which causes physical side effects such as pain and psychological impacts in the form of anxiety. Apart from that, sleep disorders can also affect the quality of life of breast cancer patients. Sleep hygiene and guided imagery therapy have been proven effective in reducing anxiety, pain and sleep disorders. Therefore, this study aims determined the difference in the effectiveness of sleep hygiene and guided imagery on anxiety and pain in breast cancer sufferers who are undergoing chemotherapy. This research uses a comparative cross-sectional design with a quasi-experimental approach. The data collection technique used purposive sampling with the Federer formula so that 16 respondents were obtained. Wilcoxon test. Before intervention the average anxiety was 63.5% and pain was 4.31%. After the intervention the average anxiety decreased to 45.81% and pain to 3.13%. The results of this study show the influence of Sleep Hygiene and Guided Imagery Therapy on anxiety and pain in breast cancer patients undergoing chemotherapy with a p value of 0.000 < 0.05.